A 1D nonlinear finite element model for analysis of composite foam-insulated concrete sandwich panels. (15th February 2019) - Lezgy-Nazargah, M.; Vidal, P.; Polit, O.
Abstract: A simple 1D nonlinear finite element model is presented for the analysis of composite foam-insulated concrete sandwich panel (FICSP) structures. The material nonlinearities of concrete wythes, steel rebar and insulation layer are considered. By employing a sinus shear deformation beam theory, the effects of transverse shear stress in concrete wythes and insulation layer are incorporated in the presented finite element formulation. The present formulation takes into account the partially composite action of FICSP structures by using the concept of distributed spring layer model. Full-scale experimental data and 3D finite element results are used to validate the developed finite element formulation. The obtained numerical results demonstrate that the presented finite element model of this study is an efficient tool to predict the detailed structural response of FICSPs till collapse stage.